If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -6 + -6x = 6x + -4 Reorder the terms: -6 + 11x + -6x = 6x + -4 Combine like terms: 11x + -6x = 5x -6 + 5x = 6x + -4 Reorder the terms: -6 + 5x = -4 + 6x Solving -6 + 5x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 5x + -6x = -4 + 6x + -6x Combine like terms: 5x + -6x = -1x -6 + -1x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + -1x = -4 + 0 -6 + -1x = -4 Add '6' to each side of the equation. -6 + 6 + -1x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -4 + 6 -1x = -4 + 6 Combine like terms: -4 + 6 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 4-7sinex=0 | | t-8=26 | | z+16=17 | | 4-7sinx=0 | | 2t-1/1-4t^2 | | 6x+2=6(3)+2 | | b+44=52 | | 4.5=1.2timesw | | 9x+2=-3+4x | | 15w^2+31w-28=0 | | 0.05x-0.03y=9 | | 6b=52 | | 7m-25=24 | | 11n+5=137 | | 51-6x=21 | | p/2=6 | | -2x-5y=20 | | 14x+6=2(5x+3) | | 2.5x+48.9=15.0-8.8x | | 2(5x-2)-x=40 | | 17x-12y=-36 | | 3xy/9x | | (m-1)x^2-2(m+1)x+m+4=0 | | 2x+1y=-10 | | -6=5-11n | | a^2+9a-9fora=-9 | | -5X+2Y=-40 | | x+2x+6x+2=29 | | (9x-4)-x=68 | | 2.2(2q+1)= | | e+10=30 | | 2x^2-12-14=0 |